Zinā in the Criminal Legislation Act (1999-2000): An Evaluation of the Implication for Muslim Women's Right in Nigeria - Akpomie, Paul Orerhime (AUC Knowledge Fountain, 2022)
The research engages in an exploration of human rights in Islam. Human rights issues are then contrasted with international law positions. The data gotten is then used for investigating women’s human rights issues in Shariʾa penal tradition regarding zinā (adultery) in Nigeria. The re-emergence of Sharia penal codes adopted by 12 Northern states in Nigeria in 1999 as an operative Islamic law has sparked concerns about rulings amounting to stoning to death in several cases of zinā. These events raised concerns about Shariʾa penal traditions’ legality and relationship with other legal traditions operational in Nigeria, a secular political space. (Chapter I) Another element presented is the discrepancy between the theoretical viewpoint on women’s human rights. How is this perspective applied to Muslim women's jurisdictions? The research uses the example of Shariʾa court cases with regard to zinā in Nigeria to illustrate the branching between theory and practice of Shariʾa penal laws. Our essay shall consider Shariʾa court proceedings and rulings of Safiyatu Hussaini and Amina Lawal cases of zinā for our research.[1] We shall focus on some of the infringed women’s rights violations articulated in the primary court sources and other secondary sources. (Chapter II) Chapter III is dedicated to evaluating the development of the court cases and ruling from the zinā, as mentioned earlier in chapter II. The analysis provides an insight into areas of human rights violations, especially against women. It demonstrates that where women and men had been prosecuted for zinā, mostly women, have been charged and convicted of the crime. Therefore, illustrating the gender biases exhibited in the court convictions and procedural neglects against the women charged. However, the paper’s research will also proffer that women’s rights in Shariʾa are not completely at odds with principles of international human rights standards of the United Nations. The argument’s postulation stems from asserting that the Islamic penal tradition is not inflexible. Based on its primary sources the Shariʾa lends itself to various explications in jurisprudence (fiqh) to help circumvent issues bordering on abuse of women’s rights in Islam. The jurisprudence of the Maliki Shariʾa Courts of Appeal in zinā cases will help illustrate this fact. (Chapter III) The research concludes by addressing the possibility of discerning the reconciliation between international rights standards and Islamic women’s rights concerns. This thesis acknowledges that there are aspects of women's violations present in zinā-related cases and establishes that there is room for reforms. However, in a pioneering manner, the essay considers a more exhaustive review of the zinā cases above to argue against the notion that it is impossible to attain any form of human rights or justice in Shariʾa courts for women. In order words, it challenges the proposition that Shariʾa penal laws are incompatible with international human rights. This research attempts to refute the position that Shariʾa penal codes are not dynamic. The Shariʾa Appeal Courts in Nigeria are saddled with the responsibility of safeguarding Shariʾa against a reductionist approach to a holistic form that is multi-valued and teleological rather than causal. Such a consideration bridges Shariʾa with regards to women's rights issues in zinā cases with the spirit of international set norms for all human rights. (Chapter IV) This thesis proposes that the Shariʾa Courts of Appeal ruling could be set as a benchmark forum for further evaluative projects of the Shariʾa criminal and penal codes procedures. Adhering to such reforms will be following the legacy of the Shariʾa committee of 1958-1962 set at bridging Shariʾa law in the penal code of 1960 with human rights concerns. The 1999 Shariʾa committee failed to meet this salient mark as discussed in chapter I. The paper ends on a note of suggestions for some considerations for Shariʾa criminal and penal reforms at ordering and safeguarding women’s rights in Nigeria.[2] [1] In 2002, Safiya Hussaini was sentenced to death by rajm under the new Shariʾa criminal codes in Sokoto. Amina Lawal was sentenced to be stoned to death for zinā in 2002. These two cases gained international recognition. [2] Before 1960 (Nigeria’s independence), Shariʾa law was fully applied in the Sokoto caliphate, northern Nigeria. It was affected by colonial rule. Shariʾa penal codes were revoked at the dawn of Nigeria’s independence in 1960. From then on, Islamic sharia law was limited to the law of family relations and personal rank. The settlement in 1960 brought these changes: The Northern courts in which her qadis (judges) administered Islamic law witnessed changes in the court systems and their judges become more Western-trained and less traditionally Muslim. In response to this trend, the program of “implementation of Shariʾa” started in 1999 in 12 Northern states. It was an attempt at restoring the status quo ante of Shariʾa before 1960.